2021
DOI: 10.1101/2021.01.26.21250274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water, sanitation, and hygiene practices and challenges during the COVID-19 pandemic: a cross-sectional study in rural Odisha, India

Abstract: Water, sanitation, and hygiene (WASH) practices emerged as a critical component to controlling and preventing the spread of the COVID-19 pandemic. We conducted 131 semi-structured phone interviews with households in rural Odisha, India to understand behavior changes made in WASH practices as a result of the pandemic and challenges that would prevent best practices. Interviews were conducted from May-July 2020 with 73 heads of household, 37 caregivers of children less than five years old, and 21 members of vill… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Whereas the study found no impact on access to water, sanitation and hygiene (WASH) services during the COVID-19 pandemic, attention still needs to be given to this area to ensure continued provision of these services in the informal settlements. Similarly, a study in India found no impact on access to sanitation and hygiene services except for water supply [60]. No impact on access to WASH services could have been because of the emphasis and investments into these services by the government and individuals since they are currently seen as a major solution to interrupt transmission of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the study found no impact on access to water, sanitation and hygiene (WASH) services during the COVID-19 pandemic, attention still needs to be given to this area to ensure continued provision of these services in the informal settlements. Similarly, a study in India found no impact on access to sanitation and hygiene services except for water supply [60]. No impact on access to WASH services could have been because of the emphasis and investments into these services by the government and individuals since they are currently seen as a major solution to interrupt transmission of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The corona virus disease of 2019 (COVID- 19) was first detected in Wuhan (Hubei, China) in December 2019. After spreading globally, COVID-19 was declared a pandemic by the World Health Organization (WHO) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the SARS-CoV-2 virus has also been detected in the feces of infected individuals. In LMICs with high rates of open defecation, ineffectual fecal sludge management, and poor access to safe drinking water, fecal-oral transmission may play a role in the virus transmission [19,20]. Therefore, the WHO strongly advocates hand hygiene as a critical control measure to contain the transmission of SARS-CoV-2 [1,16,21].…”
Section: Introductionmentioning
confidence: 99%
“…Children age early or preschool is target main in implementation life healthy because child age preschool still very active and gathering, playing together friends who do n't seldom ignore to guard main body hygiene washing hand, so they are very vulnerable to disease. Behavior washing hand done by correct is as form action for prevent the spread of Covid-19 can conducted since early to children (Bauza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reason Covid-19 transmission in children age preschool is lack of knowledge to the dangers of Covid-19, as well as how should conducted for prevent infected or transmit to the people around, so enhancement knowledge in children age Preschool is very necessary with method give education about Covid-19 and how prevention (Toros, Tart, & Falch-Eriksen, 2021) .Achild especially in children age early not yet capable To do Covid-19 prevention independent so that prevention of the Covid-19 still must controlled by parents (Odeh, Gharaibeh, Daher, Kussad, & Alassaf, 2020).Children age early or preschool is target main in implementation life healthy because child age preschool still very active and gathering, playing together friends who do n't seldom ignore to guard main body hygiene washing hand, so they are very vulnerable to disease. Behavior washing hand done by correct is as form action for prevent the spread of Covid-19 can conducted since early to children (Bauza et al, 2021).Education about Covid-19 and how prevention in children preschool could submitted by parents with give various things that can increase knowledge, abilities, and skills children (Rohita, 2020). Knowledge about prevention of Covid-19 owned by parents will impact on knowledge as well as existence will for to do actions Covid-19 prevention, attitudes and actions shown by parents will Becomes quite way effective in Introducing Covid -19 and prevention (Rohita, 2020).…”
mentioning
confidence: 99%